PENGARUH GAYA KOMUNIKASI PIMPINAN DAN LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA PEGAWAI DINAS LINGKUNGAN HIDUP KOTA PALANGKA RAYA - Putri Restu Raniarti; Anike Retawati; Muhamad Ruzaini Abdi; Aprilita (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
This study aims to analyze the influence of leadership communication style and non-physical work environment on employee performance at the Environmental Agency of Palangka Raya City. The research employed a quantitative method with a descriptive design. The research population consisted of 145 employees with a sample of 106 employees determined using the Slovin formula with purposive sampling technique. Data collection was conducted through questionnaires using a Likert scale of 1-5, and data analysis utilized Structural Equation Modeling-Partial Least Square (SEM-PLS) with SmartPLS 4.0. The results showed that leadership communication style has a positive and significant effect on employee performance with a coefficient value of 0.355 (t-statistic = 3.012; p-value = 0.001). The non-physical work environment also has a positive and significant effect on employee performance with a coefficient value of 0.582 (t-statistic = 5.701; p-value = 0.000).